Functional compounds of ginseng and ginseng-containing medicine for treating cardiovascular diseases - Liu, Lanchun; Hu, Jun; Mao, Qiyuan; Liu, Chao; He, Haoqiang; Hui, Xiaoshan; Yang, Guang; Qu, Peirong; Lian, Wenjing; Duan, Lian; Dong, Yan; Pan, Juhua; et al. (Frontiers in Pharmacology, 2022)
Traditional Chinese medicine ginseng (Panax ginseng C.A.Mey.) is the dry root and rhizome of the Araliaceae ginseng plant. It has always been used as a tonic in China for strengthening the body. Cardiovascular disease is still the main cause of death in the world. Some studies have shown that the functional components of ginseng can regulate the pathological process of various cardiovascular diseases through different mechanisms, and its formulation also plays an irreplaceable role in the clinical treatment of cardiovascular diseases. Therefore, this paper elaborates the current pharmacological effects of ginseng functional components in treating cardiovascular diseases, summarizes the adverse reactions of ginseng, and sorts out the Chinese patent medicines containing ginseng formula which can treat cardiovascular diseases.